Permainan Sepakbola Sebagai Wahana Pembinaan Sikap Sosial Anak UsiaSekolah Dasar - - Komarudin (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2005)
As a social being (homo socius), man have to interact with the surroundingenvironment. Man existence only worth when his or her existence give positive impacton how his or her social community interact and lead into a mutual life, in the otherwords a human being will positively interact with surrounding if that being have apositive social behaviour as well.A man social behaviour does not automatically emerge by itself, it has to be developedand nourish since childhood especially in the stage on elementary school. At thislevel, children start to interact with environment beside his or her own family. One ofthe best ways to develop it is through playing sport activity like soccer.Soccer games contain positive values such as teamwork, respect each other, sportive,tolerance, discipline, and iron will. These values will effect on the kid social behaviour.Which give the child positive effect on the future when interacting with the social environment.Kata Kunci: Sepakbola, Sikap Sosial, Anak Usia Sekolah Dasar.